2019
DOI: 10.3390/md17040212
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Purification of a Neuroprotective Phlorotannin from the Marine Algae Ecklonia maxima by Size Exclusion and High-Speed Counter-Current Chromatography

Abstract: Phlorotannins are polyphenolic metabolites of marine brown algae that have been shown to possess health-beneficial biological activities. An efficient approach using a combination of high-speed counter-current chromatography (HSCCC) and size exclusion chromatography with a Sephadex LH-20 has been successfully developed for the isolation and purification of a neuroprotective phlorotannin, eckmaxol, from leaves of the marine brown algae, Ecklonia maxima. The phlorotannin of interest, eckmaxol, was isolated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Table 5 summarizes the conditions employed in those studies. The ultrasound frequencies used (when reported) ranged from 20 [55,114] to 60 kHz [95], with the extraction time values ranging between 5 [55] and 90 min [115], although an UAE of 2 days has already been applied to extract phlorotannins [116]. It must be highlighted that most authors using UAE have identified the phenolic compounds extracted, contrary to most of the other novel extraction techniques.…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 5 summarizes the conditions employed in those studies. The ultrasound frequencies used (when reported) ranged from 20 [55,114] to 60 kHz [95], with the extraction time values ranging between 5 [55] and 90 min [115], although an UAE of 2 days has already been applied to extract phlorotannins [116]. It must be highlighted that most authors using UAE have identified the phenolic compounds extracted, contrary to most of the other novel extraction techniques.…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
“…At last, size exclusion chromatography (SEC-CC) using Sephadex LH-20 has been repeatedly used in the fractionation of macroalgae polar extracts [60,76,77,88,115,151,156,157,174,175,[177][178][179][180][181][182]. The separation of compounds in Sephadex LH-20 is promoted by the metabolites' molecular size, but also by its solubility in the eluent.…”
Section: Column Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their important roles in the physiology of brown algae, these compounds attracted a lot of research interest, with many studies addressing their isolation [26][27][28][29]. Moreover, as reviewed by Imbs and Zvyagintseva [30], there were a high number of studies describing the important in vitro activities of phlorotannins including anti-inflammatory, antitumor, and antibacterial activities, among others, which led researchers to advance the study of these compounds, trying to prove their biological activities in vivo.…”
Section: Phlorotanninsmentioning
confidence: 99%
“…Several studies reported neuroprotective role of astaxanthin and fucoxanthin [145, [282][283][284][285][286][287], Sargassum spp. [288][289][290][291][292][293][294][295], Saccorhiza polyschide [283], Codium tomentosum [296], Ulva spp [256,267,293,[297][298][299][300], Ecklonia maxima [256,[301][302][303], Gracilaria spp. (Figure 12) [296,[304][305][306][307][308][309][310][311], Gelidium pristoides [312,313], Halimeda incrassate [314,315], Bryothamniom triquetrum [316][317][318], Chondrus crispus ( Figure 13) [319,320], Hypnea valentiae (…”
Section: Neuroprotection In Stroke Alzheimer's and Parkinsonismmentioning
confidence: 99%